Limiting the Legality of Determining Suspects in Indonesia Pre-Trial System - Suarda, I Gede Widhiana; Taufiqurrohman, Moch. Marsa; Priambudi, Zaki (UI Scholars Hub, 2021)
This article aims to examine what the pre-trial judges consider in determining whether a suspect's determination is legal. The basis of the reason